Twenty minutes of Corsi block tapping task training does not improve mental rotation in adults with stroke - Kettlety, Sarah A.; Kibler, Giuliet L.; Hooyman, Andrew; Holl, Christina K.; Schaefer, Sydney Y.; Leech, Kristan A. (Frontiers in Neurology, 2025)
BackgroundVisuospatial function is commonly impaired post-stroke and is associated with motor learning and recovery. A single, twenty-minute Corsi Block Tapping Task (CBTT) training session improved visuospatial function in young neurotypical adults; however, it is unclear whether this training would improve visuospatial function in adults with stroke.ObjectiveTo understand if a single, twenty-minute CBTT training session improved visuospatial function in adults with stroke compared to a no-training control group of adults with stroke.MethodsParticipants post-stroke were assigned to one of two groups. The training group completed twenty minutes of computerized CBTT training. The control group completed a survey and watched a video for twenty minutes. Both groups completed a mental rotation task to assess visuospatial function pre- and post-training. To understand if training impacted mental rotation reaction time, we fit a robust mixed effects model with fixed effects for time, group, and time by group interaction. We also investigated whether lesion side impacted CBTT performance using a robust mixed effects model with fixed effects for log(time), lesion side, and log(time) by lesion side interaction.ResultsNineteen participants post-stroke were included. Neither the control nor training group improved mental rotation reaction time (time p = 0.61, group p = 0.65; interaction p = 0.52). We also found no effect of lesion side on CBTT performance [log(time) p = 0.001, lesion side p = 0.49, interaction p = 0.89].DiscussionTwenty minutes of CBTT training did not improve post-stroke mental rotation. Longer training bouts or a different type of visuospatial training may be necessary to improve visuospatial function in adults with stroke.